Beyond Community Inclusivity through Spatial Interventions - Mehan, Asma; Nawratek, Krzysztof; Tahar, Farouq (Writingplace, 2022)
This article argues against the concept of integration as the main mechanism allowing various sociocultural groups to live together and instead proposes ‘radical inclusivity’ as a better, less oppressive model of a pluralistic society. Through analytical and reflective research on the non-cohesion-based approach to integration or inclusion, this article is devoted to examining the affordances and limitations of integration through various forms of spatial interventions. As an example, we will discuss the Ellesmere Green Project in Sheffield (UK) as a typical small urban regeneration executed in a highly diverse part of Sheffield. This piece aims to bring forward the significance of moving beyond the community-as-cohesion model in urban politics and planning for integration.